(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The advancement of internet technology, cybersecurity, and the distributed system has enabled the development and establishment of electronic voting systems. This study focuses on the design and architecture of a secure and auditable electronic voting system that consists of a website, database system, and blockchain. The Ethereum blockchain is chosen due to its smart contract that is suitable for applications such as e-voting. The implementation is done using the Go language, and the Ethereum blockchain is accessible through the e-voting website. Initial testing and evaluation results show that the proposed design and architecture of the e-voting system allows a secure transaction to take place and auditable at the same time. Several configurations on the blockchain, such as block size, gas limit, and the number of sealers, could be modified to boost the performances further.